Movie viewing elicits rich and reliable brain state dynamics - Johan N. van der Meer (Nature Portfolio, 2020)
The transition from resting to perceiving one’s milieu requires a fundamental reorganization of brain activity. Here, the authors show how a fundamental reshaping of brain state dynamics supports perceptual engagement in naturalistic stimuli.